2020
DOI: 10.4236/jss.2020.85032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Technical Efficiency in the Process of Exploitation Palm Oil in Lobaye Locality, Central Africa Republic

Abstract: The present was carried out of Technical Efficiency in the Process of Exploitation Palm Oil in Lobaye Locality, Central Africa Republic. Primary data used in the study were collected through well-structured questionnaire administered with 150 randomly selected oil palm processors in the study area. Descriptive statistics, analysis and the Stochastic Frontier Production Function were used to analyze the data. The average technical efficiency of agricultural production by farmers on a variable scale of yield is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…So, the more kilogrammes of seeds processed, the more sunflower oil produced and the more technically efficient the manufacturer. These findings agree with Ngaisset and Jia [20] and Ismiasih [22] that variable capital and raw material are the most important variables in production and efficiency.…”
Section: Empirical Results Of the Stochastic Frontier Modelsupporting
confidence: 90%
See 2 more Smart Citations
“…So, the more kilogrammes of seeds processed, the more sunflower oil produced and the more technically efficient the manufacturer. These findings agree with Ngaisset and Jia [20] and Ismiasih [22] that variable capital and raw material are the most important variables in production and efficiency.…”
Section: Empirical Results Of the Stochastic Frontier Modelsupporting
confidence: 90%
“…Literature suggests that variable experience boosts production and efficiency [21,20,19]. This study found that producer experience negatively impacted technical efficiency.…”
Section: Empirical Results Of the Stochastic Frontier Modelmentioning
confidence: 68%
See 1 more Smart Citation
“…The firm with moderate efficiency has the efficiency value of above 0.7 and below 0.9. The firm is assumed as inefficient if its efficiency value is less than 0.7 5 . In Indonesia, only 1% of the farmers are efficient in their production.…”
Section: Resultsmentioning
confidence: 99%
“…The result showed that age, education and extension service significantly affect the technical efficiency. In the research of technical efficiency of palm oil in Cantral Africa Republic, the education is also an influencing factor to increase the efficiency of farmers 5 . Education and age also significantly contributed the technical efficiency of rubber farmers in Nahon, Thailand 6 .…”
Section: Introductionmentioning
confidence: 99%